(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The Hindu Society is full of a number of evils practicesand bad customs such as Dowry has become a major social evil against womentoday it is difficult to say how and why this evil custom started ? Perhaps itmight have originated from the parents desire to give their daughter a share ofher parental property in the form of Dowry. Everyday we see how women have tosuffer for the sake of Dowry. Day in & day out we read the news of one oranother young women being burnt to death because she could not bring dowry withher. Torter of young bride’s because of their failure to bring dowry is evenmore prevalent and they are forced to commit suicide. The result is that theparents of a girl have to make themselves paupers in order to arrange hermarriage.